INNOVATIVE DIGITAL PLATFORM: AN INTEGRATED INFORMATION CENTRE FOR SCHOLARSHIP IISMA-GO (Journal of Technology and Operations Management, 2025)
The number of applicants for the Indonesian International Student Mobility Awards (IISMA) rises annually, intensifying the competition. This study aims to (1) identify challenges faced by potential IISMA scholarship candidates, (2) propose solutions to address program registration preparation issues, (3) develop a business model for program registration readiness, and (4) design a prototype for program registration preparation. Employing the design thinking approach, this research addresses the issues faced by aspiring IISMA scholarship applicants, including limited integrated information, struggles to acquire comprehensive guidance and mentorship, as well as difficulties concerning language exams, essay composition, and interviews. The solutions are structured as a digital, web-based business model named "IISMA-go", encompassing segments such as registration priming, mentor consultations, discussion forums, registration guidelines, informative articles, and essential resources for students. The overall results of the USE Questionnaire indicate that IISMA-go scored 4.37 or 87.4%, signifying that this solution is highly suitable for further development as a preparation solution for IISMA scholarship registration.